Progress in Cryptology - INDOCRYPT 2008 - Rijmen, Vincent (Springer, 2017)
This book constitutes the refereed proceedings of the 9th International Conference on Cryptology in India, INDOCRYPT 2008, held in Kharagpur, India, in December 2008.